Pre-Existing Anti-Inflammatory Immune Conditions Influence Early Antibody Avidity and Isotype Profile Following Comirnaty® Vaccination in Mice - Castillo, Mariángeles (2025)
Background/Objectives: Vaccine immunogenicity is often suboptimal in vulnerable populations such as the elderly, infants, and individuals in low- and middle-income countries. One contributing factor may be pre-existing immunomodulatory conditions, including helminth infections. This study investigates the impact of Fasciola hepatica (F. hepatica) derived molecules on the early humoral response to the COVID-19 mRNA vaccine Comirnaty® in a mouse model. Methods: BALB/c mice were pretreated with a F. hepatica protein extract (FH) or complete Freund’s adjuvant (CFA) prior to vaccination. Cytokine production and antibody responses were assessed at 0, 14, and 21 days post-vaccination (dpv) through serum analysis and ex vivo splenocyte stimulation with the SARS-CoV-2 receptor-binding domain (RBD) or LPS. Results: At 0 dpv, FH-treated mice showed increased serum IL-10, while CFA treatment induced IL-12. FH- but not CFA-treated splenocytes secreted IL-10 upon RBD or LPS stimulation. At 21 dpv, FH-treated mice lacked IFN-γ production but maintained IL-10 and showed elevated IL-4, consistent with a Th2-skewed profile. Although total anti-RBD IgG levels were similar between groups, FH-treated mice exhibited reduced IgG avidity and a higher IgG1/IgG2 ratio. CFA-treated mice showed delayed avidity maturation. Conclusions: Prior exposure to F. hepatica antigens can modulate the early immune response to Comirnaty®, affecting both cellular activation and antibody quality. This altered response may reflect a reduced early protective capacity of the vaccine, which might need to be considered when designing or evaluating vaccination strategies using mRNA vaccines in helminth-endemic regions.